Public Research Organisations’ Output Vis-à-vis National Research Policy in Indonesia: Bibliometrics and Visualization - Yaniasih, Yaniasih; Rachmawati, Rulina; Sihombing, Andre (Journal of Information and Knowledge, 2017)
Public Research Organizations and universities were key players in research activities. In Indonesia, publications of Public Research Organizations were lower than universities whereas they had balanced funding. The Indonesian government had been building some strategies to improve research outputs in Indonesia by establishing national research agenda policy which encompassed national focus research areas and provision of online journal databases. This article evaluated the effectiveness of these strategies by analyzing the productivity, trend, and references of PROs publication. These analyses were conducted using bibliometrics and map visualization. The results revealed that Indonesian PROs productivity was low. Only 11% of Indonesian PROs had publications in reputed international journals. Physics science dominated the publication subject. There was a mismatch of the research area compared to the national research focus area priority. There were still many research topics which were determined as priority areas, but not many publications were produced in these areas such as research in transport and defense. The provision of journals strategy had not worked since 80% of the journal cited was unsubscribed. This study could be used to assess the effectiveness of research policy specifically for developing countries where the research budget was limited.